Digitale Disziplin: Zur Transformation der inneren Sicherheit - Meyer, Christian (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2017)
Security is one of the most dominant issues in the current political discourse. Almost every topic, ranging from the internet to migration, is being related to security. The article argues that under neoliberal conditions and given the experience of terrorist attacks, inner security turns towards more disciplinary techniques and a discourse, in which security cannot be questioned. It examens the current transformation of security in the sense of a dispositive and gives special consideration to issues of digital surveillance technologies and their relation to society. Following Foucault’s concepts of power, the article argues that discipline and governementality have to be understood within a new configuration driven by technological progress and crisis.